Correlation of Fiber Intake to Non-Fasting Blood Glucose among Overweight Women - Nuryani Nuryani (Fakultas Kedokteran Universitas Sultan Ageng Tirtayasa, 2021)
Fiber roles as a vital key in maintaining blood glucose in people with diabetes mellitus. It prevents the breaking of carbohydrates into monosaccharides and may help control blood glucose levels. In addition, fiber will make us feel full longer, so we can eat less and prevent overeating. Women have a higher risk of developing hyperglycemia than men. This study aimed to analyze the correlation between fiber intake and non-fasting blood glucose among Overweight Women. This was a quantitative study with a cross-sectional approach, conducted at the Telaga Biru Health Center, Gorontalo District, in 2019. The population was women with BMI > 25, and about 115 people were involved as the sample. The data collected was including a 24-hour recall to determine the fiber intake and blood glucose level measured by random blood glucose test using Accu blood glucose check device. Then, data were analyzed through the Chi-square Test at a significance level of p < 0.05 through SPSS for windows. Among the overweight women at Telaga Biru Public Health Center, Gorontalo, 93.9% of respondents had a low fiber intake, and 23.5% were categorized as hyperglycemic. The average daily fiber intake among respondents was 15.82 g/day, and the maximum intake was 38.90 g/day. Meanwhile, the average blood glucose level of the respondents was 126.67 mg/dL, with the minimum and maximum values were 61 mg/dL and 381.0 mg/dL. Daily fiber intake did not correlate significantly to non-fasting blood glucose levels with p-value= 0.554 (α= 0.05). Fiber intake is not significantly correlated to non-fasting high blood glucose levels within overweight women